ENGLISH WRITING SKILL OF A DEAF LEARNER AT SLB NEGERI 1 MAKASSAR - Ridwan, Ahmad; Jabu, Baso; Korompot, Chairil Anwar (Universitas Negeri Makassar, 2023)
This study aims to know the problems experienced by deaf learners in learning English writing skills and to find out how the writing skills of a deaf learner in learning English. This research is a qualitative descriptive study. The data of this study were grouped into two, namely main data consisting of introduction and documentation. Direct observation, administering tests in the form of questionnaires and English writing ability tests. Involved observation and collection of physical artifacts in the form of questionnaire results, English writing ability test results and lesson plans. The results of this study show that deaf learners can write words, phrases and sentences using a vocabulary list in English. Deaf learners can fix incomplete English sentences with the sensitivity to know the words that can be used to complete the sentence. Deaf learners are unable to make complex sentences, passive sentences and compound sentences due to the complexity of these sentences and the limitations of the research object in terms of language processing senses. Deaf learners can create simple paragraphs and create two simple coherent paragraphs using vocabulary lists and simulations of fixing incomplete sentences. Deaf learners have difficulty processing complex grammatical content. In general, paragraphs contain complex topics that are not relevant to the learning environment of the research object. Deaf learners can use the 5Ws and process consistent and coherent paragraphs using the formulas that have been discussed.